Lusoga (Lutenga). (20th January 2016) - Nabirye, Minah; de Schryver, Gilles-Maurice; Verhoeven, Jo
Abstract : Lusoga is an interlacustrine Bantu language spoken in the eastern part of Uganda in the region of Busoga, which is surrounded by the Victoria Nile in the west, Lake Kyoga in the north, the River Mpologoma in the east and Lake Victoria in the south. According to the 2002 census, this language is spoken by slightly over two million people (UBOS2006 : 12).